Influence of nickel and cobalt on microstructure of silicon solution strengthened ductile iron. (September 2015) - Weiβß, P.; Brachmann, J.; Bührig-Polaczek, A.; Fischer, S. F.
Abstract : 'Second Generation' ductile iron with a silicon content of up to 4.3 wt-% exhibits a fully ferritic matrix, which is solution strengthened by silicon. Outstanding advantages of these ductile iron grades result in their strongly increasing demand. However, due to a presumed formation of a silicon long range order, the maximum strength is limited to 600 MPa at 4.3 wt-% silicon. At higher silicon content, the mechanical properties dramatically decrease. In order to increase the maximum achievable strength, the potential of additional solution strengthening elements is subject of present research. Initially, the effects of cobalt and nickel on matrix, graphite shape and nodule count are investigated. Cobalt and nickel are identified as promising candidates for further solid solution hardening.